Recent Applications of Diversity-Oriented Synthesis Toward Novel, 3-Dimensional Fragment Collections - Kidd, Sarah L.; Osberger, Thomas J.; Mateu, Natalia; Sore, Hannah F.; Spring, David R. (Frontiers in Chemistry, 2018)
Fragment-based drug discovery (FBDD) is a well-established approach for the discovery of novel medicines, illustrated by the approval of three FBBD-derived drugs. This methodology is based on the utilisation of small “fragment” molecules (<300 Da) as starting points for drug discovery and optimisation. Organic synthesis has been identified as a significant obstacle in FBDD, however, in particular owing to the lack of novel 3-dimensional (3D) fragment collections that feature useful synthetic vectors for modification of hit compounds. Diversity-oriented synthesis (DOS) is a synthetic strategy that aims to efficiently produce compound collections with high levels of structural diversity and three-dimensionality, and is therefore well-suited for the construction of novel fragment collections. This Mini-Review highlights recent studies at the intersection of DOS and FBDD aiming to produce novel libraries of diverse, polycyclic, fragment-like compounds, and their application in fragment-based screening projects.